Proposal and Evaluation of a System Which Aims Reduction in Unexpected Collision at Non-signal Intersection - Kawatsu, Hiromi; Takaba, Sadao; Souma, Kuniaki (Systems Modeling and Simulation: Theory and Applications, 2005)
Focusing attention to the non-signal intersection in a residential area, a new traffic control system after securing a pedestrians’ safety is proposed. Reduction in the unexpected collision accident at the intersection where pedestrians are the main accident case is expectable with use of this system. In the model intersection, smoothness of the vehicles in the proposed system was evaluated by simulation, and the effectiveness of the system was shown.